Low Anticoagulant Activity of High Sulphated Heparan Sulphates - Kovensky, J; Sassetti, B; Fernández Cirelli, A; Kordich, L (Thrombosis and Haemostasis, 1990)
Two high sulphated heparin-like polysaccharides (LI, MW 16,000 and L2, MW 11,700) were isolated from rat liver tissues, after DEAE-cellulose chromatography. Heparan sulphates from heart and lung tissues were isolated for comparison and fractionated according to their molecular weight. The anticoagulant activities in vitro were studied using clotting antifactor Xa, antifactor IIa, and APTT assay methods, falling in a narrow range (5-44 IU/mg) although the wide variability m molecular weight and sulphate content. The heparan sulphate nature of fractions L1 and L2 (sulphate/disaccharide ratio 2.05 and 2.48, respectively) has been verified by: a) low iduronic/glucuronic acid ratio; b) nitrous acid degradation followed by gel chromatography; c) heparinase treatment followed by gel chromatography; d) electrophoretic behaviour. Native proteoglycans have been isolated and the glycosidic chains compared with L1 and L2. Their anticoagulant activities in vitro and the fact that antiXa clotting activity was not neutralized by protamine sulphate are in accordance with the results of structural studies.